(untitled) (Tanzania Journal for Population studies and Development, 2020)
Long waiting time in Health care facilities remains a major problem in Tanzania, mostly due to increased demand, shortage of medical health professionals and underdeveloped health care system. We attempted to estimate the average waiting time and find the best scenario in reducing out-patient waiting time. Mwananyamala Hospital was selected purposively, as a Regional government hospital in Kinondoni District, Dar es Salaam. A total of 200 selected patients attended OPD from 16th July to 15th August 2018 were observed and recorded the arrival time at each one-minute interval. Results show that patients at Mwananyamala hospital spend an average waiting time of 167 minutes, with a maximum waiting time of 243 minutes (4 hours). Simulation time was 540 minutes (9 hours) under the assumption that the OPD operates from 7:00 am to 4:00 pm. Simulation results suggested the best resource allocation at the OPD be obtained after adding two more staff, a medical doctor and a registration staff, leading to an average waiting time of 38 minutes, which is almost 4 times less than the current situation. These findings demonstrate how simulation can be used to inform hospital management with valuable data to enhance efficiency in managing outpatients.